Meta-Analysis of the Effect of Resistance Exercise Prescription on Glucose and Lipid Metabolism in Overweight and Obese Adults - SUN Yuxin; GUO Xiaoyuan; CHEN Shi; PAN Hui; ZHU Huijuan (Xiehe Yixue Zazhi)
ObjectiveTo explore the effect of resistance exercise on glycolipid metabolism in over-weight or obese people, with the aim of providing reference for the clinical development of appropriate resistance exercise programs.MethodsPubMed, Cochrane Library, EmBase, Web of Science, CNKI, Wanfang Data Knowledge Service Platform and VIP database were systematically searched to obtain the relevant literature on the effects of resistance exercise on glucose and lipid metabolism from the establishment of the library to December 31, 2023 in overweight and obese populations. The type of literature was limited to randomized controlled studies in which the exercise intervention included resistance exercise in the test group but did not include resistance exercise in the control group. The literature was screened by 2 researchers according to inclusion and exclusion criteria and relevant data were extracted.Meta-analysis of included literature was performed using RevMan 5.3 software, and publication bias was assessed using funnel plots.ResultsA total of 17 papers and 700 study subjects were included, with 351 cases in the test group, and 349 cases in the control group.Meta-analysis results showed that compared with the control group, the glycosylated hemoglobin of the test group with resistance exercise[SMD (95% CI) =-0.30(-0.53--0.07), P=0.010], fasting blood glucose[SMD (95% CI)=-0.58(-0.90--0.26), P < 0.001], insulin resistance index[SMD (95% CI) =-0.90 (-1.42--0.38), P < 0.001], and low-density lipoprotein cholesterol (LDL-C)[SMD (95% CI) =-0.28 (-0.53--0.04), P=0.020] levels were reduced.Subgroup analysis showed that the glucose metabolism levels of the test group with only resistance exercise and a combination of resistance-anaerobic exercise were significantly lower than those of the control group(both P < 0.05).The heterogeneity of the effect of resistance exercise on glucose metabolism in Asian populations(I2=57%) was smaller than that in Caucasion(I2=76%) and other populations(I2=94%), and the level of decrease in glucose metabolism indexes was significant[SMD(95% CI)=-1.15(-1.73--0.57), P < 0.001].ConclusionResistance exercise can significantly reduce the level of glycolipid metabolism indexes in overweight or obese people.